Mechanical characteristics of a lunar regolith simulant at low confining pressure - Huang, Yu; Zheng, Hu (Environmental earth sciences, 2014)
Manned lunar exploration has recently attracted renewed interest. This includes the NASA Constellation program to return humans to the Moon by 2020, the ESA Aurora program which may use the Moon as a way station to prepare for major interplanetary exploration by 2025, and the PRC program to send a human to the Moon by 2030 and build a temporary manned lunar base by 2040. One of the problems demanding a solution is the stresses on the mechanical characteristics of the lunar regolith under the microgravity environment. The gravity on the Moon is about 1/6 that on Earth. The regolith is subject to very low confining stresses under a microgravity environment and the mechanical properties can change correspondingly. Because of the limited amount of lunar regolith brought back to Earth by the Apollo missions, a lunar regolith simulant was developed using silicon carbide to investigate the properties of the lunar regolith. Based on triaxial tests, this study analyzed the mechanical properties of the lunar regolith simulant at low stresses including the shear strength, peak strength and dilatation angle. The research results provide useful information on lunar regolith characteristics for astronauts returning to the Moon and for building a temporary manned lunar base.